Studies in Guatemalan Ensifera: Mayacephalus (Orthoptera: Tettigoniidae) a new cone-headed katydid genus - Cadena-Castañeda, Oscar J.; Monzón-Sierra, José; Cortés-Torres, Carolina (Zootaxa, 2016)
Mayacephalus dickmanorum n. gen. et n. sp., from eastern Guatemala is described in this contribution. This new genus highlights from other related ones by its short tegmina; unusual for the tribe Copiphorini, and only present in three neotropical genera: Toledopizia, Brachycaulopsis and Daedalellus, being closer to the first one.